Сontrol, data collection and control distributed objects technological system - Ларін, В.Ю. (Proceedings of National Aviation University (archive), 2006)
The proposed system includes a complex of separate universal microchip devices, which measure various values, present the measuring results on digital displays, control measuring devices within the framework of a given program, transmit measuring results to a personal computer for processing, visualization and registering. Further, the described devices can control periodic intervals, conduct a real-time logical analysis, make decisions in the form of executing specific operations, related to managing various technological equipment.